2019
DOI: 10.1080/02726351.2018.1533606
|View full text |Cite
|
Sign up to set email alerts
|

Tribo-electrification of pharmaceutical powder blends

Abstract: It is well known in industrial applications involving powders and granular materials that the presence of electrostatic charges influences drastically the material flowing properties. The triboelectric charges are produced during flow at the contacts between the grains and at the contacts between the grains and the container. Unfortunately, the triboelectric effect is still poorly understood, even at the fundamental level. Therefore, the approach to solve practical problems is mostly empirical. Moreover, repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The equipment consists of a 700 mm long, 47 mm diameter V-shaped tube made of 316 L stainless steel where the powders acquire a charge when flowing through the tube. The V-tube geometry combines the different mechanisms leading to tribo-electrification: (i) friction between the grains, (ii) friction between the grains and the wall, and (iii) impact of the grains on the wall at the connection between the two tubes where the powder changes direction (Rescaglio et al, 2019). Approximately 50 ml of the powder was weighed in a glass beaker and grounded to dissipate any charge.…”
Section: Electrostatic Charge Density / Triboelectric Chargingmentioning
confidence: 99%
See 2 more Smart Citations
“…The equipment consists of a 700 mm long, 47 mm diameter V-shaped tube made of 316 L stainless steel where the powders acquire a charge when flowing through the tube. The V-tube geometry combines the different mechanisms leading to tribo-electrification: (i) friction between the grains, (ii) friction between the grains and the wall, and (iii) impact of the grains on the wall at the connection between the two tubes where the powder changes direction (Rescaglio et al, 2019). Approximately 50 ml of the powder was weighed in a glass beaker and grounded to dissipate any charge.…”
Section: Electrostatic Charge Density / Triboelectric Chargingmentioning
confidence: 99%
“…Particle triboelectric charging (electrostatics) is a physical effect frequently ignored but can occur with pharmaceutical powders and APIs (Rescaglio et al, 2019;Š upuk et al, 2012;Wong et al, 2015). Factors which influence powder charging can be: type of surface material, contact area, surface roughness, surface cleanliness, chemical structure, absorbed moisture, particle size distribution, shape, roughness, crystallinity and surface area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…115 The optimal formulation estimate that complies with a set of requirements of other selected properties and save excipients can be obtained using numerous ML techniques, as comprehensibly reviewed recently by Gao et al 114 and Yang et al 262 Powder flow behavior, for example, is a key factor to assess the potential for the manufacturability of oral solid dosage forms in drug development (e.g., tablet), 263 which is attractive due to its fewer unit operations involved in the production and its convenience for the patient. 264 Flowability is a problematic property to measure and predict, especially in the context of small particle sizes and uncontrolled shape distributions, 263 electrostatic forces, 265 and varying surface properties. 266 Predicting powder flow behavior opens possibilities to fine-tune the crystallization process with reduced risks in the feasibility of downstream processing and easier scale-up.…”
Section: Filterability Flowability Tabletability and Final Product Mi...mentioning
confidence: 99%
“…Choi et al (2017) found that when the moisture content of the drug powder is lower than 5 wt%, the charge‐to‐mass ratio of the powder begins to increase. Rescaglio et al (2019) study proved that the net charge of the drug mixture is a complex function of the relative amount of active pharmaceutical ingredient in the mixture, and the number and sign of the drug powder charge depend on the material in contact with the powder. Woodhead and Armour‐Chélu (2003) studied the charging characteristics of alumina particles in pipeline transportation and found that a decrease in temperature and an increase in relative humidity usually lead to a decrease in the charge level.…”
Section: Introductionmentioning
confidence: 99%